The effectiveness of Plusmiles loyalty program for Plusmiles card in enhancing customer awareness / Mohd Azrul Syafiq Mohd Zikri - Mohd Zikri, Mohd Azrul Syafiq (Faculty of Business and Management, 2010)
Generally, loyalty program is a part of the promotion strategies to communicating with the public in an attempt to influence them toward buying your products and/or services. Promotion is the broader, all inclusive term. Promotion, as a general term, includes all the ways available to make a product and/or service known to and purchased by customers and clients. The word promotion is also used specifically to refer to a particular activity that is intended to promote the business, product or service. A store might advertise that it's having a big promotion on certain items, for instance, or a business person may refer to an ad as a promotion.